Design and Analysis of Large Scale Log Studies - Dumais, Susan; Jeffries, Robin; Russell, Daniel M.; Tang, Diane; Teevan, Jaime (CHI 2011 (Course), 2011)
Logging user behavior is a crucial aspect of understanding how people actually use online systems. Yet a large number of HCI practitioners have not had a great deal of exposure to the issues involved in obtaining, cleaning, interpreting or analyzing large log file data sets. In this CHI 2011 course, five experts in very-large-scale logs analysis will present the ways and means for CHI attendees to gather and analyze log data.